PENGARUH BUDAYA ORGANISASI, PENDIDIKAN DAN PELATIHAN, MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN INDRAGIRI HILIR - Rais, Indra Yevi (Jurnal Tepak Manajemen Bisnis, 2014)
The purpose of this study was to determine the effect of organizational culture, education and training, and motivation on employee performance at the Manpower and T ransmigration Indragiri Hilir, either partially or simultaneously. Samples from this study wer e all employees at the Department of Manpower and T ransmigration Indragiri Hilir in 2014, amounting to 67 people. This study uses the method of testing multiple linear regression, F-test and t-test. F test was used to analyze the effect of independent variables on the dependent variable simultaneously / synchronously, while the t-test to analyze the effect of independent variables on the dependent variable partially with a significant level of 5%. The results of this study indicate that the variable of organizational culture, education and training, and motivation simultaneously significant effect on employee performance. It can be seen from the value of F calculated value greater propagators F table. While partially only education and training variables that significantly influence the performance of employees, while the variable organizational culture and motivation variables had no significant effect on employee performance.Keywords: employee performance, organizational culture, education and training, and motivation